3D-printed porous titanium scaffolds incorporating niobium for high bone regeneration capacity. (September 2020) - Liang, Hang; Zhao, Danlei; Feng, Xiaobo; Ma, Liang; Deng, Xiangyu; Han, Changjun; Wei, Qingsong; Yang, Cao
Abstract: Biomimetic functionalization is a pressing need for orthopedic implants to achieve reinforced osseointegration and accelerated osteogenesis, thereby obtaining a successful clinical outcome. To realize bioactivity, TiNb alloys with varying Nb contents (0–45 at.%) were additively manufactured using elemental powder blends. The regulation of the Nb contents could balance the surface constituent ratio of Nb2 O5 and TiO2, enhancing the formation of the hydroxyl group and surface hydrophilicity. Moreover, the effect mechanism of Nb2 O5 on immune modulation and bone regeneration was first put forward. The incorporation of Nb improved the viability of macrophages by inducing a macrophage polarization toward an anti-inflammatory M2-like state. The variation of morphological and up-regulated expression of anti-inflammatory factors led to a more favorable osteoimmune microenvironment for osteogenesis, promoting the osteogenic differentiation of osteoblasts in vitro . Considering the surface constituent and in vitro biological performance, 3D-printed Ti25Nb scaffolds were placed into the femoral condyle of the rabbit. The Micro-CT and histological analysis indicated that Ti25Nb scaffolds could accelerate bone regeneration and reinforce bone integration as relative to pure Ti. Overall, the Ti25Nb scaffold exhibited structural bionic ability, surprising immunomodulatory properties, superior bone regeneration and osseointegration capacity, showing exceptional potential in the treatment of bone defects. Graphical abstract: Unlabelled Image Highlights: TiNb scaffolds were in-situ synthesized using selective laser melting. Nb addition enhanced the formation of Nb2 O5 and associated surface hydrophilicity. Nb2O5 activated the anti-inflammatory macrophage and promoted osteogenic differentiation. TiNb scaffolds presented reinforced osseointegration and accelerated osteogenesis.